Socialization and Self-Determination in Different-Age Dyads of Students who Are Deafblind. (May 2016) - Bruce, Susan M.; Zatta, Mary C.; Gavin, Mary; Stelzer, Sharon
Introduction: Deafblindness limits access to social cues and social feedback, thus restricting the development of social skills. Many children with CHARGE syndrome, a leading cause of deafblindness, experience challenges with emotional self-regulation and anxiety that may interfere with socialization. Learning about self-determination skills such as goal setting, problem solving, and choice making, in the context of socialization instruction, may improve emotional regulation and social skills. Methods: This collaborative action research study employed grounded theory design, with ongoing data analysis. The primary research question was: How will interactions between adolescent students with CHARGE syndrome and younger students with mixed etiologies of deafblindness change over time, in the context of an arranged interaction space? Data sources were videotaped observations of interaction and feedback sessions, evaluation forms, and field notes. Independent qualitative analysis by two raters and member checks enhanced the trustworthiness of findings. Results: The younger students learned to make toy choices when presented with them by the adolescent students. Joint attention challenges occurred, as adolescent students did not understand their pals' visual latency and play skills. The adolescent students learned to interact more effectively with younger students while rehearsing self-determination skills such as goal setting and problem solving. Discussion: Adult support was essential to successful interactions and to adolescent students' engagement in self-reflection and self-evaluation during the feedback sessions. More research is needed on socialization and self-determination instruction of children who are deafblind, including those with CHARGE syndrome. Implications for practitioners: Children who are deafblind require direct instruction for social skills and opportunities to practice interactions with differently aged children. They also require opportunities to problem solve in the context of socialization opportunities. Support from familiar adults may reduce the anxiety experienced during socialization.